Heat-insulating and resistance-reducing pipeline anticorrosive paint as well as preparation method and application thereof

By developing a pipeline anti-corrosion coating that combines heat insulation, drag reduction and corrosion resistance, the corrosion and energy consumption problems faced by metal pipes in complex use environments has been solved, and significant performance improvement and cost reduction have been achieved.

CN119799110APending Publication Date: 2025-04-11WUHAN HAOSHENG TECHNOLOGY GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411985326.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Metal pipes face corrosion and energy consumption problems in complex use environments, resulting in shorter service life and increased construction costs.

Method used

Develop a pipe anti-corrosion coating that combines heat insulation, drag reduction and corrosion resistance. Through the synergy between component A and component B, the performance of the coating is improved. Component A includes functional emulsions such as fluoropolymer emulsions and high temperature resistant resin emulsions, and component B includes functional fillers and cementitious materials such as zinc powder, glass flakes and ultrafine low alkali cement.

Benefits of technology

It significantly reduces the resistance and heat loss of pipeline liquid transportation, improves corrosion resistance, and can withstand high concentration of acid and alkali corrosion for a long time, far exceeding the performance of traditional single-function coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a heat-insulating and resistance-reducing pipeline anticorrosive coating as well as a preparation method and application thereof, and belongs to the technical field of building coatings. The heat-insulating and resistance-reducing anticorrosive paint for the pipeline comprises a component A and a component B, wherein the component A is prepared from the following raw materials: fluorine-containing polymer emulsion, high-temperature-resistant resin emulsion, polysiloxane emulsion, petroleum resin emulsion, a polydimethylsiloxane flatting agent and a defoaming agent; the component B is prepared from the following raw materials: zinc powder, glass flakes, hollow glass beads, superfine low-alkali cement, nano silicon dioxide aerogel, aluminum oxide ceramic powder, graphene powder, triisopropanolamine powder and aluminum powder. The heat-insulation and resistance-reduction pipeline anticorrosive paint provided by the invention has the three functions of heat insulation, resistance reduction and corrosion prevention, each function far exceeds the performance index of a traditional single paint, and when the heat-insulation and resistance-reduction pipeline anticorrosive paint is applied to a metal pipeline, the resistance of pipeline liquid conveying can be remarkably reduced, the heat loss of the pipeline is reduced, and the service life of the pipeline is prolonged. The anti-corrosion performance of the metal pipeline is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building coatings, and in particular to a heat-insulating, drag-reducing pipeline anticorrosive coating and a preparation method and application thereof. Background Art

[0002] Pipeline transportation plays a significant role in cross-regional resource allocation and promoting economic development in my country. However, metal pipelines face various corrosion phenomena and energy consumption problems in complex use environments, which not only seriously affect the service life of the pipelines, but also increase unnecessary costs. Take the oil pipeline as an example. During long-distance oil transportation, the friction between the crude oil and the inner wall of the pipeline will reduce the flow rate of the crude oil. In order to maintain the transportation volume, it is often necessary to increase the transportation pressure. At the same time, if the pipeline is not well insulated, heat loss will cause the viscosity of the crude oil to increase, which requires greater power to transport. The use of thermal insulation and drag reduction coatings can reduce dependence on booster stations and reduce construction costs.

[0003] Therefore, the present invention provides a heat-insulating and drag-reducing pipeline anti-corrosion coating, which combines the three functions of heat insulation, drag reduction and corrosion prevention to reduce production and construction costs. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a thermal insulation and drag reduction pipeline anti-corrosion coating, and a preparation method and application thereof. Compared with traditional single-function coatings, the coating of the present invention takes into account the three functions of thermal insulation, drag reduction and corrosion resistance, and each function far exceeds the performance indicators of traditional single-function coatings. Among them, the thermal insulation performance can greatly reduce the heat loss of liquid transportation in the pipeline. For liquids within 200°C, the surface temperature of the coating is not higher than 45°C; the drag reduction performance can greatly reduce the kinetic energy loss of liquid transportation in the pipeline, and the friction coefficient is small; the anti-corrosion performance is higher than that of traditional epoxy resin products, and can withstand high-concentration acid and alkali corrosion for a long time.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] A heat-insulating and drag-reducing pipeline anticorrosive coating, comprising components A and B, wherein the raw materials of component A include, by mass percentage: 65% to 75% of fluorine-containing polymer emulsion, 10% to 20% of high-temperature resistant resin emulsion, 5% to 10% of polysiloxane emulsion, 2% to 8% of petroleum resin emulsion, 0.5% to 1.0% of polydimethylsiloxane leveling agent, and 0.8% to 1.5% of defoaming agent;

[0007] The raw materials of component B include, by mass percentage: zinc powder 25%~35%, glass flakes 10%~20%, hollow glass microspheres 15%~25%, ultrafine low-alkali cement 15%~25%, nano-silica aerogel 2%~6%, alumina ceramic powder 4%~8%, graphene powder 1%~3%, triisopropanolamine powder 3%~7%, aluminum powder 0.2%~0.8%;

[0008] The mass ratio of the A and B components is 1:(1.0~1.5).

[0009] The heat-insulating and drag-reducing pipeline anti-corrosion coating of the present invention comprises components A and B, wherein the raw materials of component A comprise functional emulsions and auxiliary materials, and the raw materials of component B comprise functional fillers and binders; the fluoropolymer emulsion in component A can effectively enhance the anti-corrosion performance of the coating, the polysiloxane emulsion can reduce the contact angle between the coating and the pipeline surface, reduce the surface energy, and reduce the surface resistance, and the high-temperature resistant resin emulsion can keep the coating from aging and failure at high temperatures. The three functional emulsions can be compounded in a specific proportion to synergistically and significantly improve the anti-corrosion, drag-reduction and high-temperature resistance performance of the coating. The zinc powder in component B is highly active. During the metal corrosion process, it can "sacrifice" and preferentially form an oxide layer to protect the metal structure. During the metal or concrete corrosion process, the glass flakes prevent the corrosive medium from contacting the surface of the structure through the "maze effect". Hollow glass microspheres can significantly reduce the thermal conductivity of the coating due to their hollow structure. Nano-silica aerogel has a light weight and extremely low thermal conductivity due to its unique spatial structure. Graphene powder itself has high corrosion resistance. In the coating, it can reduce the consumption rate of zinc powder by improving the conductivity and improve the effective utilization rate of zinc powder. Alumina ceramic powder has the characteristics of high temperature resistance and corrosion resistance. Combining it with high temperature resistant resin, that is, organic Combined with inorganic materials, it can further improve the high temperature resistance of the coating; aluminum powder has high reflectivity and excellent weather resistance. It can reflect various types of light radiation in the coating, reduce radiation heat absorption and enhance the weather resistance of the coating; ultrafine low-alkali cement mainly plays a bonding role, which can not only effectively bond various types of powders in component B together, but also play a good promoting role in the emulsion curing process. Its ultrafine characteristics can make the force between particles more uniform and the bonding force stronger. Its low alkali characteristics can make the coating more stable and avoid the occurrence of alkali-aggregate reaction; after the triisopropanolamine powder is dissolved, it can directly promote the curing of high temperature resistant resin, and indirectly promote the curing of fluororesin, silicone resin and petroleum resin.

[0010] Preferably, the fluorine-containing polymer emulsion includes at least one of fluorine acrylate polymer emulsion, polytetrafluoroethylene polymer emulsion and fluorocarbon polymer emulsion.

[0011] Preferably, the high temperature resistant resin emulsion includes at least one of dicyclopentyl dioxide epoxy resin emulsion, methacrylate epoxy emulsion, and methyl metaborate epoxy emulsion.

[0012] Preferably, the polysiloxane emulsion includes at least one of methyl alkyl polysiloxane emulsion, octamethyl cyclotetrasiloxane emulsion and terminal hydroxyl polydimethylsiloxane emulsion.

[0013] Preferably, the petroleum resin includes C9 petroleum resin and / or C5 petroleum resin.

[0014] Preferably, the solid content of the fluorine-containing polymer emulsion is 45-55%.

[0015] Preferably, the solid content of the high temperature resistant resin emulsion is 45-55%.

[0016] Preferably, the solid content of the polysiloxane emulsion is 30-45%.

[0017] Preferably, the solid content of the petroleum resin emulsion is 30-45%.

[0018] Preferably, the defoamer includes at least one of a polyether defoamer, an inorganic silicon defoamer and an organic silicon defoamer.

[0019] Preferably, the zinc powder is spherical zinc powder or flake zinc powder with a size of 5 to 20 μm.

[0020] Preferably, the hollow glass microspheres are hollow glass microspheres with a diameter less than 20 μm.

[0021] The preparation method of the heat-insulating and drag-reducing pipeline anticorrosive coating comprises the following steps:

[0022] Preparation of component A: Mix fluorine-containing polymer emulsion, high temperature resistant resin emulsion and polysiloxane emulsion to obtain mixture I; mix petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I with mixture II, add defoaming agent and mix to obtain component A, and seal and store for later use;

[0023] Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0024] When in use, component A and component B are mixed evenly according to a mass ratio to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0025] The invention also provides application of the anti-corrosion coating in metal pipelines.

[0026] Compared with the prior art, the present invention is beneficial in that:

[0027] The heat-insulating and drag-reducing pipeline anti-corrosion coating of the present invention is used for metal pipelines, which can significantly reduce the resistance of pipeline liquid transportation, reduce the heat loss of pipelines, and improve the anti-corrosion performance of metal pipelines; compared with traditional single-function coatings, the heat-insulating and drag-reducing pipeline anti-corrosion coating takes into account the three functions of heat insulation, drag reduction, and corrosion protection, and each function far exceeds the performance indicators of traditional single-function coatings, among which the heat-insulating performance can greatly reduce the heat loss of liquid transportation in the pipeline, and the surface temperature of the coating is not higher than 45°C for liquids within 200°C; the drag-reducing performance can greatly reduce the kinetic energy loss of liquid transportation in the pipeline, and the friction coefficient is small; the anti-corrosion performance is higher than that of traditional epoxy resin products, and can withstand high-concentration acid and alkali corrosion for a long time. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides a heat-insulating and drag-reducing pipeline anticorrosive coating, comprising components A and B, wherein component A comprises, by mass percentage: 65% to 75% of fluorine-containing polymer emulsion, 10% to 20% of high-temperature resistant resin emulsion, 5% to 10% of polysiloxane emulsion, 2% to 8% of petroleum resin emulsion, 0.5% to 1.0% of polydimethylsiloxane leveling agent, and 0.8% to 1.5% of defoaming agent;

[0030] Component B includes, by mass percentage: zinc powder 25%~35%, glass flakes 10%~20%, hollow glass microspheres 15%~25%, ultrafine low-alkali cement 15%~25%, nano-silica aerogel 2%~6%, alumina ceramic powder 4%~8%, graphene powder 1%~3%, triisopropanolamine powder 3%~7%, aluminum powder 0.2%~0.8%;

[0031] The mass ratio of the A and B components is 1:(1.0~1.5).

[0032] In some examples, the fluorine-containing polymer emulsion includes at least one of a fluoroacrylate polymer emulsion, a polytetrafluoroethylene polymer emulsion, and a fluorocarbon polymer emulsion.

[0033] In some examples, the high temperature resistant resin emulsion includes at least one of dicyclopentyl ether dioxide epoxy resin emulsion, methacrylate epoxy ester emulsion, and methyl metaborate epoxy emulsion.

[0034] In some examples, the polysiloxane emulsion includes at least one of methyl alkyl polysiloxane emulsion, octamethyl cyclotetrasiloxane emulsion, and terminal hydroxyl polydimethylsiloxane emulsion.

[0035] In some examples, the petroleum resin includes C9 petroleum resin and / or C5 petroleum resin.

[0036] In some examples, the defoamer includes at least one of a polyether defoamer, an inorganic silicone defoamer, and an organic silicone defoamer.

[0037] In some examples, the zinc powder is spherical zinc powder or flake zinc powder with a size of 5-20 μm.

[0038] In some examples, the hollow glass microspheres are hollow glass microspheres with a diameter less than 20 μm.

[0039] In some examples, the solid content of the fluorine-containing polymer emulsion is 45-55%; the solid content of the high temperature resistant resin emulsion is 45-55%; the solid content of the polysiloxane emulsion is 30-45%; and the solid content of the petroleum resin emulsion is 30-45%.

[0040] In the following specific examples, the solid content of the fluorine-containing polymer emulsion is 50%; the solid content of the high temperature resistant resin emulsion is 50%; the solid content of the polysiloxane emulsion is 35%; and the solid content of the petroleum resin emulsion is 35%.

[0041] In the following specific examples, unless otherwise specified, all raw materials and reagents used were purchased conventionally.

[0042] Example 1

[0043] A heat-insulating and drag-reducing pipeline anticorrosive coating, composed of two components A and B, wherein the component A comprises, by mass percentage: 70% fluoroacrylate polymer emulsion, 15% dicyclopentyl dioxide epoxy resin emulsion, 8% methyl alkyl polysiloxane emulsion, 5% C5 petroleum resin emulsion, 0.8% polydimethylsiloxane leveling agent, and 1.2% silicone defoaming agent;

[0044] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 20% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 4% nano-silica aerogel, 6% alumina ceramic powder, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0045] The preparation method is as follows:

[0046] (1) Preparation of component A: Mix fluoroacrylate polymer emulsion, dicyclopentyl ether dioxide epoxy resin emulsion, and methyl alkyl polysiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I with mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0047] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0048] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0049] Example 2

[0050] A heat-insulating and drag-reducing pipeline anticorrosive coating, composed of two components A and B, wherein the component A includes, by mass percentage: 75% polytetrafluoroethylene polymer emulsion, 10% methacrylate epoxy emulsion, 10% octamethylcyclotetrasiloxane emulsion, 2.5% C5 petroleum resin emulsion, 1.0% polydimethylsiloxane leveling agent, and 1.5% polyether defoaming agent;

[0051] Component B includes, by mass percentage, 32% flaky zinc powder of 5-20 μm, 17% 100 mesh glass flakes, 15% hollow glass microspheres of 15 μm in diameter, 15% ultrafine low-alkali cement, 6% nano-silica aerogel, 5% alumina ceramic powder, 3% graphene powder, 6.2% triisopropanolamine powder, and 0.8% aluminum powder.

[0052] The preparation method is as follows:

[0053] (1) Preparation of component A: Mix polytetrafluoroethylene polymer emulsion, methacrylate epoxy ester emulsion and octamethylcyclotetrasiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I and mixture II, add polyether defoamer and mix to obtain component A, and seal and store for later use;

[0054] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0055] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.5 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0056] Example 3

[0057] A heat-insulating and drag-reducing pipeline anticorrosive coating, composed of two components A and B, wherein component A includes, by mass percentage: 68% fluorocarbon polymer emulsion, 14% methyl metaborate epoxy emulsion, 10% terminal hydroxyl polydimethylsiloxane emulsion, 6.7% C5 petroleum resin emulsion, 0.5% polydimethylsiloxane leveling agent, and 0.8% inorganic silicon defoaming agent;

[0058] Component B includes, by mass percentage: 25% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 25% hollow glass microspheres of 10 μm in diameter, 24.8% ultrafine low-alkali cement, 2% nano-silica aerogel, 4% alumina ceramic powder, 1% graphene powder, 3% triisopropanolamine powder, and 0.2% aluminum powder.

[0059] The preparation method is as follows:

[0060] (1) Preparation of component A: Mix fluorocarbon polymer emulsion, methyl borate epoxy emulsion and hydroxyl-terminated polydimethylsiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I and mixture II, add inorganic silicone defoaming agent and mix to obtain component A, which is sealed and stored for later use;

[0061] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0062] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0063] Comparative Example 1

[0064] A coating, composed of two components A and B, wherein the component A comprises, by mass percentage, 85% of dicyclopentyl dioxide epoxy resin emulsion, 8% of methyl alkyl polysiloxane emulsion, 5% of C5 petroleum resin emulsion, 0.8% of polydimethylsiloxane leveling agent, and 1.2% of organic silicon defoaming agent;

[0065] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 20% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 4% nano-silica aerogel, 6% alumina ceramic powder, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0066] The preparation method is as follows:

[0067] (1) Preparation of component A: Mix biscyclopentyl ether dioxide epoxy resin emulsion and methyl alkyl polysiloxane emulsion to obtain mixture I; Mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; Mix mixture I and mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0068] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0069] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0070] Comparative Example 2

[0071] A coating, composed of two components A and B, wherein the component A comprises, by mass percentage, 78% of fluoroacrylate polymer emulsion, 15% of dicyclopentyl dioxide epoxy resin emulsion, 5% of C5 petroleum resin emulsion, 0.8% of polydimethylsiloxane leveling agent, and 1.2% of silicone defoaming agent;

[0072] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 20% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 4% nano-silica aerogel, 6% alumina ceramic powder, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0073] The preparation method is as follows:

[0074] (1) Preparation of component A: Mix fluoroacrylate polymer emulsion and dicyclopentyl ether dioxide epoxy resin emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I and mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0075] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0076] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0077] Comparative Example 3

[0078] The preparation method of the coating of this comparative example is basically the same as the preparation method of the coating in Example 1, except that, in the preparation of component A, an equal amount of fluoroacrylate polymer emulsion is used to replace the dicyclopentyl ether dioxide epoxy resin emulsion, and the rest remains unchanged.

[0079] A coating, composed of two components A and B, wherein the component A comprises, by mass percentage, 85% of fluoroacrylate polymer emulsion, 8% of methyl alkyl polysiloxane emulsion, 5% of C5 petroleum resin emulsion, 0.8% of polydimethylsiloxane leveling agent, and 1.2% of organic silicon defoaming agent;

[0080] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 20% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 4% nano-silica aerogel, 6% alumina ceramic powder, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0081] The preparation method is as follows:

[0082] (1) Preparation of component A: Mix fluoroacrylate polymer emulsion and methyl alkyl polysiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I and mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0083] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0084] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0085] Comparative Example 4

[0086] A coating, composed of two components A and B, wherein the component A comprises, by mass percentage, 70% of fluoroacrylate polymer emulsion, 15% of dicyclopentyl dioxide epoxy resin emulsion, 8% of methyl alkyl polysiloxane emulsion, 5% of C5 petroleum resin emulsion, 0.8% of polydimethylsiloxane leveling agent, and 1.2% of silicone defoaming agent;

[0087] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 24% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 6% alumina ceramic powder, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0088] The preparation method is as follows:

[0089] (1) Preparation of component A: Mix fluoroacrylate polymer emulsion, dicyclopentyl ether dioxide epoxy resin emulsion, and methyl alkyl polysiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I with mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0090] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0091] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0092] Comparative Example 5

[0093] A coating, composed of two components A and B, wherein the component A comprises, by mass percentage, 70% of fluoroacrylate polymer emulsion, 15% of dicyclopentyl dioxide epoxy resin emulsion, 8% of methyl alkyl polysiloxane emulsion, 5% of C5 petroleum resin emulsion, 0.8% of polydimethylsiloxane leveling agent, and 1.2% of silicone defoaming agent;

[0094] Component B includes, by mass percentage: 30% spherical zinc powder of 5-20 μm, 15% 100 mesh glass flakes, 26% hollow glass microspheres of 15 μm in diameter, 17.5% ultrafine low-alkali cement, 4% nano-silica aerogel, 2% graphene powder, 5% triisopropanolamine powder, and 0.5% aluminum powder.

[0095] The preparation method is as follows:

[0096] (1) Preparation of component A: Mix fluoroacrylate polymer emulsion, dicyclopentyl ether dioxide epoxy resin emulsion, and methyl alkyl polysiloxane emulsion to obtain mixture I; mix C5 petroleum resin emulsion and polydimethylsiloxane leveling agent to obtain mixture II; mix mixture I with mixture II, add silicone defoamer and mix to obtain component A, and seal and store for later use;

[0097] (2) Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B, which is sealed and stored for later use;

[0098] (3) When in use, component A and component B are mixed evenly in a mass ratio of 1:1.2 to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

[0099] Performance Testing

[0100] The coatings of Examples 1 to 3 and Comparative Examples 1 to 5 were tested for performance, wherein the thermal conductivity was tested according to the standard method GB / T17371, and when the average temperature was 350±5°C, the thermal conductivity was ≤0.10 W / (m·K) and was considered qualified, and when the average temperature was 70±5°C, the thermal conductivity was ≤0.06 W / (m·K) and was considered qualified; the anti-corrosion performance was tested according to the standard method GB / T31361, and was considered qualified if there was no blistering or cracking; the appearance and drag reduction performance were tested according to the standard methods ASTM D523 and ASTM D968A, and the appearance coefficient was ≥50 and the wear coefficient was ≥23. The test results are shown in Table 1.

[0101] Table 1: Performance test results of Examples 1 to 3 and Comparative Examples 1 to 5

[0102]

[0103] It can be seen from Table 1 that the performance indicators of the thermal insulation and drag reduction pipeline anti-corrosion coatings of Examples 1 to 3 of the present invention all meet or even far exceed the indicator requirements of the standards in GB / T17371, GB / T31361, ASTM D523 and ASTM D968A, indicating that the thermal insulation and drag reduction pipeline anti-corrosion coatings of Examples 1 to 3 of the present invention have good thermal insulation, anti-corrosion and drag reduction properties.

[0104] Compared with Example 1, Comparative Example 1 uses an equal amount of dicyclopentyl ether dioxide epoxy resin emulsion to replace the fluoroacrylate polymer emulsion (that is, the coating of Comparative Example 1 does not contain fluoroacrylate emulsion), and the anti-corrosion performance of the prepared coating is significantly reduced. The coating was immersed in a 10% sulfuric acid solution at 45°C, and blistering and cracking occurred after about 12 days; and the thermal insulation and drag reduction properties of the prepared coating are also inferior to those of the coating in Example 1; the results show that the fluoropolymer emulsion plays an indispensable role in improving the anti-corrosion and thermal insulation and drag reduction properties of the coating of the present invention. In Comparative Example 2, an equal amount of fluoroacrylate polymer emulsion is used to replace the methyl alkyl polysiloxane emulsion (i.e., the coating of Comparative Example 2 does not contain methyl alkyl polysiloxane emulsion). The appearance and wear coefficient performance of the prepared coating are significantly reduced, far from meeting the standard requirements. Among them, the appearance standard value is reduced from 75 to 36, and the wear coefficient is reduced from 34 to 15; and the thermal insulation and anti-corrosion properties of the prepared coating are also affected to varying degrees; the results show that the polysiloxane emulsion in the coating of the present invention plays an indispensable role in improving the drag reduction performance of the pipeline and maintaining good thermal insulation and anti-corrosion properties. In Comparative Example 3, an equal amount of fluoroacrylate polymer emulsion is used to replace the dicyclopentyl ether dioxide epoxy resin emulsion (that is, the coating of Comparative Example 3 does not contain dicyclopentyl ether dioxide epoxy resin emulsion). The thermal insulation performance of the prepared coating is significantly reduced, and the thermal conductivity at 350±5°C is increased from 0.07 to 0.29, and the thermal conductivity at 70±5°C is increased from 0.03 to 0.17; and the anti-corrosion and drag reduction properties of the prepared coating are also slightly reduced; the results show that the high temperature resistant resin emulsion in the coating of the present invention plays an indispensable role in improving the thermal insulation performance of the pipeline and maintaining good anti-corrosion and drag reduction properties. Comparative Example 4 uses an equal amount of hollow glass microspheres to replace nano-silica aerogel, and Comparative Example 5 uses an equal amount of hollow glass microspheres to replace alumina ceramic powder. Due to the decrease in the high temperature resistance of the coating, the thermal conductivity at 350°C increases significantly, which may be related to the failure of the high temperature resistant resin in the coating and the deformation and failure of the internal structure. In addition, after the alumina ceramic powder is replaced by hollow glass microspheres, the strong acid resistance of the coating also decreases significantly, and bubbling and cracking occur. The results show that nano-silica aerogel and alumina ceramic powder play an important role in the high temperature resistance and corrosion resistance of the coating.

[0105] In summary, the thermal insulation and drag reduction pipeline anti-corrosion coating of the present invention includes two components A and B, wherein the raw materials of component A include functional emulsion and auxiliary materials, and the raw materials of component B include functional fillers and binders. Components A and B work synergistically, so that when the thermal insulation and drag reduction pipeline anti-corrosion coating is used for metal pipelines, it can significantly reduce the resistance of pipeline liquid transportation, reduce the heat loss of the pipeline and improve the anti-corrosion performance of the metal pipeline; compared with traditional single-functional coatings, the thermal insulation and drag reduction pipeline anti-corrosion coating of the present invention takes into account the three functions of heat insulation, drag reduction and corrosion protection, and each function far exceeds the performance indicators of traditional single-function coatings, and has broad application prospects.

[0106] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A heat-insulating and drag-reducing pipeline anticorrosion coating, characterized in that: It includes components A and B, wherein component A includes, by mass percentage: 65% to 75% fluorine-containing polymer emulsion, 10% to 20% high temperature resistant resin emulsion, 5% to 10% polysiloxane emulsion, 2% to 8% petroleum resin emulsion, 0.5% to 1.0% polydimethylsiloxane leveling agent, and 0.8% to 1.5% defoaming agent; Component B includes, by mass percentage: zinc powder 25%~35%, glass flakes 10%~20%, hollow glass microspheres 15%~25%, ultrafine low-alkali cement 15%~25%, nano-silica aerogel 2%~6%, alumina ceramic powder 4%~8%, graphene powder 1%~3%, triisopropanolamine powder 3%~7%, aluminum powder 0.2%~0.8%; The mass ratio of the A and B components is 1:(1.0~1.5).

2. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1 is characterized in that: The fluorine-containing polymer emulsion includes at least one of a fluorine acrylate polymer emulsion, a polytetrafluoroethylene polymer emulsion, and a fluorocarbon polymer emulsion.

3. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1 is characterized in that: The high temperature resistant resin emulsion includes at least one of dicyclopentyl dioxide epoxy resin emulsion, methacrylate epoxy ester emulsion and methyl metaborate epoxy emulsion.

4. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1, characterized in that: The polysiloxane emulsion includes at least one of methyl alkyl polysiloxane emulsion, octamethyl cyclotetrasiloxane emulsion and terminal hydroxyl polydimethylsiloxane emulsion.

5. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1 is characterized in that: The petroleum resin includes C9 petroleum resin and / or C5 petroleum resin.

6. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1, characterized in that: The defoamer includes at least one of a polyether defoamer, an inorganic silicon defoamer and an organic silicon defoamer.

7. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1 is characterized in that: The zinc powder is spherical zinc powder or flaky zinc powder with a size of 5 to 20 μm.

8. The heat-insulating and drag-reducing pipeline anticorrosion coating according to claim 1, characterized in that: The hollow glass microspheres are hollow glass microspheres with a diameter less than 20 μm.

9. A method for preparing a heat-insulating and drag-reducing pipeline anticorrosive coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of component A: fluorine-containing polymer emulsion, high temperature resistant resin emulsion and polysiloxane emulsion are mixed evenly to obtain mixture I; petroleum resin emulsion and polydimethylsiloxane leveling agent are mixed evenly to obtain mixture II; mixture I and mixture II are mixed, and a defoaming agent is added and mixed evenly to obtain component A; Preparation of component B: glass flakes, hollow glass microspheres, ultrafine low-alkali cement, nano-silica aerogel, alumina ceramic powder, graphene powder, and triisopropanolamine powder are mixed evenly, and then zinc powder and aluminum powder are added and mixed evenly to obtain component B; When in use, component A and component B are mixed evenly according to a mass ratio to obtain a heat-insulating and drag-reducing pipeline anti-corrosion coating.

10. Use of the anti-corrosion coating prepared by the method as claimed in claim 9 in metal pipelines.